A bi-stable nonlinear energy sink using the cantilever bi-stable hybrid symmetric laminate. (1st March 2023) - Li, Ming; Li, Yanqi; Liu, Xiaohui; Dai, Fuhong
Abstract: This paper develops a new bi-stable nonlinear energy sink (BNES) only consisting of the cantilever bi-stable hybrid symmetric laminate (BHSL) and tip masses. This BNES has advantages of light weight, simple and reliable structure, since it does not need external devices or magnets to maintain its bi-stable characteristic. A finite element model (FEM) is developed to perform static and dynamic analyses of a harmonically excited linear oscillator coupled with BNES. An equivalent theoretical model is developed to model the coupled system based on the relationship between the restoring force and the displacement of BHSL. The Runge-Kutta method is used to perform direct numerical solutions. Different types of the steady-state response for BNES contain the local and global periodic motions, the local and global strongly modulated responses and chaos, while the primary object exhibits the periodic motion and the strongly modulated response. The effects of the excitation amplitude, the tip mass of BNES, the lay-up design and the length of BHSL are considered on the dynamic responses and vibration suppression efficiency of BNES. The results show adjusting these parameters and lay-up designs can improve the vibration suppression efficiency of BNES. In addition, the experimental prototype is prepared and verifies the rightness of the finite element model and theoretical model.